Neoplecostomus (Teleostei: Loricariidae) from the upper Rio Paraná basin, Brazil, with description of three new species - Zawadzki, Cláudio Henrique; Pavanelli, Carla Simone; Langeani, Francisco [UNESP] (Magnolia Press, 2008)
Neoplecostomus paranensis was the only Neoplecostomus species known from the upper Rio Paraná basin, and it was diagnosed from its congeners mainly by the absence or reduction of the adipose fin. In this study we describe three new Neoplecostomus species. All of them are promptly differentiated from N. paranensis by having a well-developed adipose fin. Furthermore, the new species are differentiated from congeners by morphometric and meristic traits, in addition to color pattern. Neoplecostomus paranensis is redescribed. We also provide an identification key to all Neoplecostomus species. Copyright © 2008 Magnolia Press.
Keywords: Catfishes; Freshwater; Ichthyology; Neotropical; Ostariophysi; Siluriformes